2004
DOI: 10.1097/01.qai.0000137371.80695.ef
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Antiviral Activity of AMD3100, a Selective CXCR4 Receptor Inhibitor, in HIV-1 Infection

Abstract: AMD3100 is a CXCR4 receptor inhibitor with anti-HIV-1 activity in vitro. We tested the safety, pharmacokinetics, and antiviral effect of AMD3100 administered for 10 days by continuous intravenous infusion in an open-label dose escalation study from 2.5 to 160 microg/kg/h. Forty HIV-infected patients with an HIV RNA level >5000 copies/mL on stable antiretroviral (ARV) regimens or off therapy were enrolled. Syncytium-inducing (SI) phenotype in an MT-2 cell assay was required in higher dose cohorts. Most subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
245
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(258 citation statements)
references
References 43 publications
4
245
1
7
Order By: Relevance
“…However, an unexpected rapid, transient leukocytosis was noticed during phase I/II clinical trials of AMD3100 in volunteers and HIV-infected patients, caused by the mobilization of various hematopoietic cells, including CD34-positive HSC, to the blood. 87,88 In the second trial in HIV patients, one patient receiving the highest dose of AMD3100 (160 mg/kg/h) had a significant drop in his viral load, but overall the efficacy of AMD3100 in affecting disease activity in HIV-1 patients was considered low and therefore this application was not further pursued for AMD3100. Instead, AnorMED explored AMD3100 as a mobilizing agent for HSC, 88 and a subsequent series of preclinical and clinical trials demonstrated that AMD3100 alone and in combination with G-CSF mobilizes HSC.…”
Section: Non-peptide Cxcr4 Antagonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an unexpected rapid, transient leukocytosis was noticed during phase I/II clinical trials of AMD3100 in volunteers and HIV-infected patients, caused by the mobilization of various hematopoietic cells, including CD34-positive HSC, to the blood. 87,88 In the second trial in HIV patients, one patient receiving the highest dose of AMD3100 (160 mg/kg/h) had a significant drop in his viral load, but overall the efficacy of AMD3100 in affecting disease activity in HIV-1 patients was considered low and therefore this application was not further pursued for AMD3100. Instead, AnorMED explored AMD3100 as a mobilizing agent for HSC, 88 and a subsequent series of preclinical and clinical trials demonstrated that AMD3100 alone and in combination with G-CSF mobilizes HSC.…”
Section: Non-peptide Cxcr4 Antagonistsmentioning
confidence: 99%
“…87,88 In the second trial in HIV patients, one patient receiving the highest dose of AMD3100 (160 mg/kg/h) had a significant drop in his viral load, but overall the efficacy of AMD3100 in affecting disease activity in HIV-1 patients was considered low and therefore this application was not further pursued for AMD3100. Instead, AnorMED explored AMD3100 as a mobilizing agent for HSC, 88 and a subsequent series of preclinical and clinical trials demonstrated that AMD3100 alone and in combination with G-CSF mobilizes HSC. 34,89,90 AMD3100 (recently re-named as Plerixafor or Mozobil) is now owned by Genzyme Corporation (Cambridge, MA, USA) after a recent takeover of AnorMED by Genzyme in late 2006.…”
Section: Non-peptide Cxcr4 Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…During these trials, it was observed that plerixafor elicited a transient leukocytosis in healthy volunteers as well as HIV-1-infected individuals. 14,15 Subsequently, the role of plerixafor in the mobilization of PBSCs for auto-SCT was explored. 16,17 Plerixafor has been shown to rapidly increase circulating CD34 þ progenitor cells in preclinical murine models and healthy volunteers alone or in combination with G-CSF.…”
Section: Introductionmentioning
confidence: 99%
“…On pouvait donc s'attendre à ce que le simple blocage, c'est-à-dire l'inhibition, de CXCR4 par des antirétroviraux donne lieu à des effets secondaires non acceptables, excluant l'utilisation à long terme d'antagonistes de CXCR4. L'effet le plus marqué de ce genre d'interventions thérapeutiques est la mobilisation de cellules souches hématopoïé-tiques de la moelle osseuse qui migrent alors dans la circulation sanguine [14]. Cet effet de mobilisation pourrait devenir intéressant pour des traitements de courte durée dans un contexte de greffe de cellules hématopoïétiques [15].…”
Section: Cxcr4 Cible Thérapeutique Prometteuse Mais Délicateunclassified